Clinical Impact of Hypercalcemia in Kidney Transplant. (26th May 2011) - Messa, Piergiorgio; Cafforio, Cosimo; Alfieri, Carlo
Abstract : Hypercalcemia (HC) has been variably reported in kidney transplanted (KTx) recipients (5–15%). Calcium levels peak around the 3rd month after KTx and thereafter slightly reduce and stabilize. Though many factors have been claimed to induce HC after KTx, the persistence of posttransplant hyperparathyroidism (PT-HPT) of moderate-severe degree is universally considered the first causal factor. Though not proven, there are experimental and clinical suggestions that HC can adversely affect either the graft (nephrocalcinosis) and other organs or systems (vascular calcifications, erythrocytosis, pancreatitis, etc.). However, there is no conclusive evidence that correction of serum calcium levels might avoid the occurrence of these claimed clinical effects of HC. The best way to reduce the occurrence of HC after KTx is to treat as best we can the secondary hyperparathyroidism (SHP) during the uraemic stages. The indication to Parathyroidectomy (PTX), either before or after KTx, in order to prevent or to treat, respectively, HC after KTx, is still a matter of debate which has been revived by the availability of the calcimimetic cinacalcet for the treatment of PT-HPT. However, we still need to better clarify many points as regards the potential adverse effects related to either PTX or cinacalcet use in this clinical set, and we are waiting for the results of future randomized controlled trials to achieve some more definite conclusions on this topic.